THE APPLICATION OF COOPERATIVE LEARNING MODEL TGT TYPE IN IMPROVING LEARNING RESULT OF MATHEMATICS AT FOURTH GRADE STUDENT IN STATE ELEMENTARY SCHOOL 1 LEMBUPURWO 2012/2013 ACADEMIC YEAR - MINTARWATI, OKTAVIANA HADI (KALAM CENDEKIA PGSD KEBUMEN, 2015)
The research aims to: Describe the application of Cooperative Learning Model TGT Type and find problems and solutions. This research method is Classroom Action Research (CAR) that consists three cycles with  subject 22 student. The problems in this research that requires a lot of time so that the teachers should manage the time of each stage learning well. The result shows that : The Application of Cooperative Learning Model TGT Type can Improving Learning Result of Mathematics.